Substitution between net and gross settlement systems: A concern for financial stability? - Ben Craig; Falko Fecht (Deutsche Bundesbank, 2011)
While net settlement systems make more efficient use of liquidity than gross settlement systems, they are known to generate systemic risk. What does that tendency imply for the stability of the payments [or financial] system when the two settlement systems coexist? Do liquidity shortages induce banks to settle more transactions in net settlement system, thereby increasing systemic risk? Or do banks require their counterparties to send payments through gross settlement system when default risks are high, increasing the need for liquidity and the money market rate but reducing overall systemic risk? This paper studies the factors that drive the relative importance of net and gross settlement systems over the short run, using daily data on transaction volumes from the large-volume payment systems of all euro area countries that have had both a net and a gross settlement system at the same time. Applying a large portfolio of different econometric techniques, we find that it is actually the transactions volumes in gross settlement systems that affect the daily price of liquidity and the credit risk spread in money markets.
Keywords: E44; G21; 330; Payment System; financial stability; interbank market; financial contagion; Zahlungsverkehr; Internationaler Zahlungsverkehr; Bankenliquidität; Geldmarkt; Bankenkrise; Finanzmarktkrise; Eurozone